Self-focused attention and safety behaviours maintain social anxiety in adolescents: An experimental study - Leigh, Eleanor (PLoS One, 2021)
BACKGROUND: Self-focused attention and safety behaviours are both associated with adolescent social anxiety. In adults, experimental studies have indicated that the processes are causally implicated in social anxiety, but this hypothesis has not yet been tested in a youth sample. METHODS: This experiment explored this possibility by asking high and low socially anxious adolescents (N = 57) to undertake conversations under different conditions. During one conversation they were instructed to focus on themselves and use safety behaviours, and in the other they focused externally and did not use safety behaviours. Self-report, conversation partner report and independent assessor ratings were taken. RESULTS: Self-focus and safety behaviours increased feelings and appearance of anxiety and undermined performance for all participants, but only high socially anxious participants reported habitually using self-focus and safety behaviours. CONCLUSIONS: The findings provide support for the causal role of self-focus and safety behaviours in adolescent social anxiety and point to the potential clinical value of techniques reversing them to treat the disorder.